Metacognitive strategies in education: Fostering self-regulated learning across disciplines and learning environments - M. Ali, Salah (Journal of Interdisciplinary Studies in Education, 2026)
Effective self-regulated learning (SRL) is key to academic success, and metacognitive strategies are essential in supporting it across disciplines. This study investigates how metacognitive strategies enhance SRL in online and traditional classrooms. Employing a mixed-methods design, this study analyzed data from questionnaires, educator interviews, and classroom observations involving 300 students. The results show that the use of metacognitive strategies is positively correlated with academic success, with variation across learning environments. Educators reported inconsistent integration of strategies, underscoring the need for standardized approaches. The study recommends tailored solutions: digital tools for online self-regulation and collaborative activities for traditional settings. The study advocates for educator training programs to systematically embed metacognitive strategies into instruction.